Alcohol use and HIV suppression after completion of financial incentives for alcohol abstinence and isoniazid adherence: a randomized controlled trialResearch in context - Winnie R. Muyindike; Robin Fatch; Sara Lodi; Nneka I. Emenyonu; Allen Kekibiina; Julian Adong; Brian Beesiga; Kara Marson; Harsha Thirumurthy; Michael G. McDonell; Moses R. Kamya; Gabriel Chamie; et al. (EClinicalMedicine)
Summary: Background: In a recent randomized trial, six months of financial incentives contingent for recent alcohol abstinence led to lower levels of hazardous drinking, while incentives for recent isoniazid (INH) ingestion had no impact on INH adherence, during TB preventive therapy among persons with HIV (PWH). Whether the short-term incentives influence long-term alcohol use and HIV viral suppression post-intervention is unknown. Methods: We analyzed twelve-month HIV viral suppression and alcohol use in the Drinkers’ Intervention to Prevent Tuberculosis study, a randomized controlled trial among PWH with latent TB and unhealthy alcohol use in south-western Uganda. We randomly assigned 680 participants (1:1:1:1) initiating six months of INH to: Arm 1, no incentives (control); Arm 2, financial incentives contingent on recent alcohol abstinence; Arm 3, incentives contingent on recent INH use; and Arm 4, incentives for recent alcohol abstinence and INH use, rewarded separately. The 6 months post-intervention outcomes evaluated were pre-specified and included: HIV viral suppression (<200 copies/mL) and no/low alcohol use, defined as Alcohol Use Disorders Identification Test-Consumption negative (<3: women, <4: men) and phosphatidylethanol, an alcohol biomarker, <35 ng/mL. We estimated adjusted risk differences (aRD) for alcohol reduction and INH adherence interventions using multivariable logistic regression adjusting for randomization stratification factors (sex and study site), and baseline alcohol use (alcohol intervention model only). Clinicaltrials.gov registration: NCT03492216, Registered 04/10/2018. Findings: Of 600 participants with 12-month viral load results, 556/585 (95%) with baseline results were virally suppressed, and 583/600 (97%) were virally suppressed at 12-months. Twelve-month viral suppression did not differ significantly between either intervention group versus control (alcohol reduction incentives versus control aRD = −0.9% (95% CI: −3.6 to 1.7); INH adherence incentives versus control aRD = 2.2% (95% CI: −0.4 to 4.9)). Of the 617 participants with 12-month alcohol use measures, alcohol reduction incentives led to a significantly greater proportion with no/low alcohol use at 12-months (20.2% [64/317]) versus no alcohol reduction incentives (11.0% [33/300]); aRD = 8.4%, (95% CI: 3.3–13.4), p = 0.001. Interpretation: Viral suppression was high (>95%) at baseline and at 12 months: we found no effect of either 6-month alcohol reduction or INH adherence incentives on long-term viral suppression. Six months of alcohol reduction incentives were effective at promoting no/low alcohol use at 12 months, demonstrating persistent effects post-intervention. Funding: National Institutes of Health (NIH/NIAAA) U01AA026223 (PI: Hahn) and U01AA026221 (PI: Chamie), NIH/NIAAA K24 AA022586 (PI: Hahn), NIH/NIAAA K24 AA031211 (PI: Chamie), Providence/Boston Center for AIDS Research P30AI042853 (PI: Sara Lodi).